Simmental-Hereford cross calves - M. McKee; R.R. Schalles; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1971)
Data on nine Simmental-Hereford cross calves (3 bulls and 6 females) from birth to 6 months of age was reported in Bulletin 536. The three bulls shared conditions with three Hereford, four Angus, and one Shorthorn bull. The six cross heifers grew with three Hereford, three Angus, and two Shorthorn heifers.
Keywords: Cattlemen& #x27; s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Weaning; Simmental-Hereford cross